Five novel NF1 gene pathogenic variants in 10 different Chinese families with neurofibromatosis type 1. Issue 9 (25th July 2019) - Chen, Linlin; Xue, Feng; Xu, Jia; He, Jinwei; Fu, Wenzhen; Zhang, Zhenlin; Kang, Qinglin
Abstract: Background: Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder with equal sex incidence that is characterized by neurofibromas, café‐au‐lait macules, axillary freckling, optic pathway tumor, distinctive osseous lesion, and iris Lisch nodules. Inactivating variants in the NF1 gene have been identified to be correlated with NF1. This tumor suppressor gene is located at 17q11.2. Methods: Ten affected NF1 probands and their available relatives from 10 unrelated Chinese families with neurofibromatosis type 1 were clinically studied. All of these probands mainly complained of osseous lesions. PCR was used to analyze and sequence the variants. We collected both laboratory and radiological information. Results: We detected five novel pathogenic variants including two de novo variants in these 10 families: one missense variant, p.Cys709Arg(c.2125T>C), in exon 18 and four frameshift variants: p.Leu1459Profs*2(c.4436dupT) in exon 34; p.Lys99Argfs*4(c.296delA) in exon 4; p.Leu762Cysfs*2(c.2283delA) in exon 19; and p.Leu1522Ilefs*53(c.4562_4563dupAT) in exon 34. Conclusion: Novel pathogenic variants in the NF1 gene in these families correlated with the phenotype and genotype and explained the clinical manifestations of these patients. The results help us to understand the genetic basis of patients with neurofibromatosis type 1 in China. Our study expands the pathogenic variant spectrum of the NF1 gene and may be helpful in genetic counseling and prenatal genetic diagnosis. Abstract : We detected five novel mutations including two de novo mutations in these 10 families with Neurofibromatosis type 1. All of these probands mainly complaint about osseous lesions.